2005
DOI: 10.1111/j.1525-1497.2005.0096.x
|View full text |Cite
|
Sign up to set email alerts
|

Placebo HAART regimen as a method for teaching medication adherence issues to students

Abstract: Placebo medication regimens may help educate students about adherence issues. In this randomized trial, 23 third-year medical students took a 2-week placebo regimen mimicking highly active antiretroviral therapy (HAART) during their medicine clerkship; 15 students served as controls. Although no effect was demonstrated from this intervention on an evaluation instrument examining attitudes and beliefs about medication nonadherence, all 23 student-subjects agreed in postintervention interviews that the experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Of the three, only one evaluated student learning and assessed the effect of the experience. [27][28][29] Results of this 6-year retrospective study indicate that students have received this simulation project well. Furthermore, the goal of increasing awareness of polypharmacy and adherence concerns appears to have been met.…”
Section: Valuementioning
confidence: 84%
See 1 more Smart Citation
“…Of the three, only one evaluated student learning and assessed the effect of the experience. [27][28][29] Results of this 6-year retrospective study indicate that students have received this simulation project well. Furthermore, the goal of increasing awareness of polypharmacy and adherence concerns appears to have been met.…”
Section: Valuementioning
confidence: 84%
“…Additionally, a literature review revealed three publications about teaching adherence to medical student using a simulation experience. Of the three, only one evaluated student learning and assessed the effect of the experience 27–29 …”
Section: Discussionmentioning
confidence: 99%
“…Students valued the experience and significantly improved their insight, attitude, and recognition towards medication adherence and its related challenges. 7 In a study by Serag-Bolos and colleagues, an oncology simulation significantly improved pharmacy student therapeutic knowledge. 4 One way to use a simulation event alongside of a TBL session that would allow for a better reinforcement of student knowledge would be to have a debriefing session with the students immediately following the simulation with a faculty member to allow for reinforcement or correction of observed concepts and skills.…”
Section: Critical Analysismentioning
confidence: 99%
“…Slain (2002) Instructions to take the placebo with or without food to experience the added difficulty of specific medication directions. Sutton (2005) Placebos were intentionally selected to closely resemble the capsules and tablets of a HAART regimen to increase the authenticity of the experience. Chen (2008) In addition to taking a placebo regimen, participants used earplugs to simulate difficulty hearing, were given medication instructions written in intelligible font and therefore requiring another student to decipher, and slept on the floor to simulate homelessness.…”
Section: Interdisciplinary Experiencesmentioning
confidence: 99%